Simultaneous Determination of Thirteen Aminoalcohol-Diterpenoid Alkaloids in the Lateral Roots of Aconitum carmichaeli by Solid-Phase Extraction-Liquid Chromatography–Tandem Mass Spectrometry - Ding, Jia-Yu; Liu, Xiu-Xiu; Xiong, Dong-Mei; Ye, Li-Ming; Chao, Ruo-Bing (Planta Medica, 2014)
Aminoalcohol-diterpenoid alkaloids have been reported as the cardioactive components in the lateral roots of Aconitum carmichaeli (Fuzi) according to recent studies. Determination of these effective components is of great significance for quality control purposes for Fuzi. Here we report, for the first, the development and validation of a new method to determine the 13 aminoalcohol-diterpenoid alkaloids in Fuzi by using a simple and accurate solid-phase extraction-liquid chromatography-tandem mass spectrometry. The chromatographic analysis was performed on an ODS column with methanol-0.1 % formic acid (80 : 20, v/v) as the mobile phase. The quantification was performed using MS/MS detection in the positive ion mode with multiple reaction monitoring. Linearity was observed within a range of concentrations of 20–2000 ng/mL. For all the analytes, the r value was greater than 0.9990. The limit of detection and the limit of quantitation were less than 0.5 ng/mL and 2.0 ng/mL, respectively. The intraday and interday precisions were less than 5 % and 10 %, respectively. The accuracy was within the range of 90 to 105 %. This method was successfully applied to determine the 13 aminoalcohol-diterpenoid alkaloids in Fuzi from different origins and with different processing methods.
Keywords: aminoalcohol-diterpenoid alkaloids; Aconitum carmichaeli; Ranunculaceae; SPE-LC-MS/MS; content determination